Determination of the Spin Axis in Quantum Spin Hall Insulator Candidate Monolayer WTe_{2} - Wenjin Zhao (American Physical Society, 2021)
Evidence for the quantum spin Hall effect (QSHE) has been reported in several experimental systems, in the form of edge conductance approaching a quantized value at zero magnetic field. However, another fundamental feature of the QSHE, that of spin-momentum locking in the edge channel, has not been demonstrated. Here, we report that in an applied magnetic field the edge conductance in monolayer WTe_{2}, a candidate QSHE material, is suppressed by the component of the field perpendicular to a particular axis, implying that the spin in the edge states lies along this axis. Surprisingly, the axis is independent of edge orientation, chemical potential, and sample, being fixed relative to the monolayer crystal structure, lying at (40±2)° to the layer normal within the mirror plane. This finding is consistent with a theoretical model in which the bulk bands nearest the Fermi energy have the same parity, leading to simple spin texture with a single, momentum-independent spin axis that is inherited by the edge modes. In addition, the results strengthen the case for spin-momentum locking and, therefore, that monolayer WTe_{2} is a natural two-dimensional topological insulator exhibiting the QSHE.